Adsorption of amphetamine on deep eutectic solvents functionalized graphene oxide/metal-organic framework nanocomposite: Elucidation of hydrogen bonding and DFT studies. (May 2023) - Liu, Yujie; Cao, Shurui; Liu, Zhenghong; Wu, Duanhao; Luo, Mengni; Chen, Zhiqiong
Abstract: The efficient and selective removal of amphetamine (AMP) from water bodies is significant for environmental remediation. In this study, a novel strategy for screening deep eutectic solvent (DES) functional monomers was proposed based on density functional theory (DFT) calculations. Using magnetic GO/ZIF-67 (ZMG) as substrates, three DES-functionalized adsorbents (ZMG-BA, ZMG-FA, and ZMG-PA) were successfully synthesized. The isothermal results showed that the DES-functionalized materials introduced more adsorption sites and mainly contributed to the formation of hydrogen bonds. The order of the maximum adsorption capacity ( Q m ) was as follows: ZMG-BA (732.110 μg⋅g −1 ) > ZMG-FA (636.518 μg⋅g −1 ) > ZMG-PA (564.618 μg⋅g −1 ) > ZMG (489.913 μg⋅g −1 ). The adsorption rate of AMP on ZMG-BA was the highest (98.1%) at pH 11, which could be explained by the less protonation of –NH2 from AMP being more favorable for forming hydrogen bonds with the –COOH of ZMG-BA. The strongest affinity of the –COOH of ZMG-BA for AMP was reflected in the most hydrogen bonds and the shortest bond length. The hydrogen bonding adsorption mechanism was fully explained by experimental characterization (FT-IR, XPS) and DFT calculations. Frontier Molecular Orbital (FMO) calculations showed that ZMG-BA had the lowest HOMO-LUMO energy gap ( E gap ), the highest chemical activity and the best adsorption capability. The experimental results agreed with the results of theoretical calculations, proving the validity of the functional monomer screening method. This research offered fresh suggestions for the functionalized modification of carbon nanomaterials to achieve effective and selective adsorption for psychoactive substances. Graphical abstract: Image 1 Highlights: Magnetic GO/ZIF-67 materials functionalized with DES were successfully prepared by DFT-assisted design. The DES-functionalized adsorbents exhibited a good adsorption capacity, selectivity and reusability for amphetamine. Kinetic and isotherm studies had been carried out to characterize amphetamine adsorption performance. Hydrogen-bonding interaction played an important role in the adsorption process of amphetamine. The adsorption mechanisms were explored by combining experiments and density functional theory (DFT) simulations.